Influence of Customer Relationship Management on RelationshipQuality at Abdul Wahab Sjahranie Hospital - Sumarni Sumarni; Ratno Adrianto; Chaerunnisa Chaerunnisa; Eka Putri Rahayu (Mulawarman International Conference on Tropical Public Health, 2025)
As hospital competition and service demands rise, patient loyalty becomes a critical asset. Therefore, understanding how Customer Relationship Management (CRM) influences Relationship Quality (RQ) is essential. CRM is no longer just an administrative tool; it is a core strategy to strengthen RQ. By improving understanding, interaction, and personalization, CRM directly builds the trust, satisfaction, and commitment that form a strong RQ, which is the foundation for patient loyalty. This study analyzes the influence of Customer Relationship Management on Relationship Quality in inpatient services at Abdul Wahab Sjahranie Hospital. Method Using a quantitative analytical survey design, data were collected from 390 purposively selected inpatients who had visited the hospital at least twice in the past six months. A closed-ended Likert scale questionnaire was used, and data were analyzed with the Chi-Square tests and Logistic Regression were included. The results show that Customer Knowledge, Customer Knowledge Management Capability, and Customization have a significant effect on RQ, while Customer Interaction has no significant effect. Overall, RQ plays a central role as a mediator, where the application of the Customer Relationship Management strategy is significantly able to strengthen the loyalty of inpatients at Abdul Wahab Sjahranie Samarinda Hospital through the formation of quality relationships. These findings highlight that understanding patients comprehensively, effectively managing patient knowledge, and tailoring services to patient needs are strategic in strengthening hospital–patient relationships. Practical implications suggest prioritizing CRM strategies focused on patient needs and experiences to foster long-term, mutually beneficial relationships.